Effect of acute hypoxia on regional cerebral blood flow: effect of sympathetic nerve activity - Lewis, Nia C. S. (American Physiological Society, 2014)
We examined 1) whether global cerebral blood flow (CBF) would increase across a 6-h bout of normobaric poikilocapnic hypoxia and be mediated by a larger increase in blood flow in the vertebral artery (VA) than in the internal carotid artery (ICA); and 2) whether additional increases in global CBF would be evident following an α(1)-adrenergic blockade via further dilation of the ICA and VA. In 11 young normotensive individuals, ultrasound measures of ICA and VA flow were obtained in normoxia (baseline) and following 60, 210, and 330 min of hypoxia (Fi(O(2)) = 0.11). Ninety minutes prior to final assessment, participants received an α(1)-adrenoreceptor blocker (prazosin, 1 mg/20 kg body mass) or placebo. Compared with baseline, following 60, 220, and 330 min of hypoxia, global CBF [(ICA(Flow) + VA(Flow)) ∗ 2] increased by 160 ± 52 ml/min (+28%; P = 0.05), 134 ± 23 ml/min (+23%; P = 0.02), and 113 ± 51 (+19%; P = 0.27), respectively. Compared with baseline, ICA(Flow) increased by 23% following 60 min of hypoxia (P = 0.06), after which it progressively declined. The percentage increase in VA flow was consistently larger than ICA flow during hypoxia by ∼20% (P = 0.002). Compared with baseline, ICA and VA diameters increased during hypoxia by ∼9% and ∼12%, respectively (P ≤ 0.05), and were correlated with reductions in Sa(O(2)). Flow and diameters were unaltered following α(1) blockade (P ≥ 0.10). In conclusion, elevations in global CBF during acute hypoxia are partly mediated via greater increases in VA flow compared with ICA flow; this regional difference was unaltered following α(1) blockade, indicating that a heightened sympathetic nerve activity with hypoxia does not constrain further dilation of larger extracranial blood vessels.